PEMIKIRAN PENDIDIKAN ISLAM ETIKA GLOBAL, ETIKA SOSIAL DAN PERSAUDARAAN UMMAT MANUSIA - Saprun, Saprun; Nurhakim, Moh.; Risman, Kadar (Ibtida'iy : Jurnal Prodi PGMI, 2024)
This article aims to examine and analyze the Islamic view of Muslim brotherhood which in certain phenomena causes differences and divisions. The focus of the problem is the frequent emergence of new currents that claim to be Muslims, causing friction in conflict in society. This research was conducted through Library Research through documentation studies and literature reviews online or offline. The results showed that the authors found There is an Islamic contribution to the above phenomenon that Islam teaches the importance of building a just, empathetic, and relatable society at both the local and global levels. These concepts became the foundation for the formation of global ethics, social ethics, and the unity of mankind in the view of Islam